Implementation of Fuel Oil Purchase Permits for Fishermen in Badung Regency - Dewa Made Ashadi Cahyadi; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Service of purchasing permit for diesel oil and oil for fishermen is one of the important aspects that support fisheries and marine activities in Indonesia. Diesel oil and oil are used by fishermen to operate boats and fishing gear, which are basic needs for the continuity of their business. This service process generally involves several steps and administrative requirements that must be met. Here is an explanation of this permit service The diesel and oil purchase permit service aims to ensure that fishermen have proper access to fuel and lubricants at reasonable prices and according to their needs Related Parties The Badung Regency Fisheries Service, which is managed by the UPTD Kedonganan Fish Marketing Place, South Kuta District, is usually responsible for issuing permits or recommendations for fishermen who want to buy diesel at subsidized prices or certain prices. Fishermen's Registration Permit Application Process Flow: Fishermen must be registered in the system as legitimate fishermen, usually by showing proof of ownership or a fishery business license (SIUP). The central and regional governments have an important role in regulating and supervising the distribution of fuel to fishermen. Guidance for fishermen regarding the permit application procedure and an understanding of their rights and obligations is also carried out periodically. This aims to improve the efficiency of resource use and prevent misuse of the subsidy program Reasons for Choosing This Topic Some areas or fishing ports that are far from fuel distribution centers often experience supply shortages. This causes fuel shortages in the area, even though fishermen already have official permits and some fishermen feel that the fuel quota given does not match their operational needs, especially if the fishing season is not supportive. This makes fishermen lack fuel when they need to go to sea The research method used in this study is to use a qualitative method using a descriptive approach. Data collection techniques use observation, interviews, and documentation. The technique for determining informants used is by using a purposive sampling technique which obtains informants in the form of Heads of UPTD Fish Marketing Places, Fishermen, and other related parties The expected outcome is that improvements are needed in the bureaucratic system, increased fuel distribution to remote areas, and increased supervision to prevent misuse of fuel subsidies.Keywords: Badung Regency Fisheries Service, Fishermen, UPTD TPI Kedonganan